Climatic and Ecological Change in the Americas: Reseña de libro - Kirmes, Eva Sophia (Notas de Antropología de las Américas, 2025)
Reseña de libro / Review of the book: Whitaker, Armstrong & Odonne (eds.): Climatic and Ecological Change in the Americas : A Perspective from Historical Ecology, 2023. London: Routdlege, 256 p., ISBN: 9781003316497, Open Access.